Change of Pathological Type to Metaplastic Squamous Cell Carcinoma of the Breast During Disease Recurrence: Case Report and Literature Review - Guo, Tianhui; Chen, Zhiying; Xu, Jinpeng; Zhang, Yongchun (Frontiers in Oncology, 2020)
Background: Metaplastic squamous cell carcinoma (SCC) of the breast is a rare and heterogeneous group of primary breast malignancies. The etiology, pathogenesis and proper treatment for this kind rare breast cancer are still unclear. Case presentation: We reported a case of a 55-year-old women with a palpable lump in the inner quadrant of the right breast. She underwent a right breast mass enlargement resection and sentinel lymph node biopsy, which indicated the tumor was the invasive ductal carcinoma, following by 4 cycles of doxorubicin plus cyclophosphamide and 4 cycles of docetaxel as adjuvant chemotherapy, then simultaneous integrated boost intensity modulated radiotherapy to the whole right breast. After 2-years follow-up, she had biopsy-proven disease recurrence in the right breast which revealed squamous cell carcinoma, and mammogram showed abnormalities in the lower inner quadrant of the right breast and left axillary lymph nodes. Then we performed bilateral breast modified radical mastectomy which confirmed the recurrent tumors were metaplatic squamous cell carcinoma, following by the adjuvant chemotherapy and the adjuvant raidotherapy of the left supraclavicular and apical axillary regions. There has been no recurrent or metastatic evidence in the 16 months follow-up since the second surgery. Conclusion: This case report shows the possible pathogenesis and immunohistochemical analysis for recurrent metaplastic SCC of the breast, which indicates the possible switching of pathological phenotype. Surgery with adjuvant therapy may be a proper therapeutic strategy for recurrent primary SCC of the breast.